Electrochemical supercapacitive studies of chemically deposited Co1-xNixS thin films. (1st March 2020) - Chavan, G.T.; Yadav, A.A.; Kamble, S.S.; Sabah, F.A.; Prakshale, V.M.; Sikora, A.; Warycha, J.; Bulakhe, R.N.; In, Insik; Cho, Eun-Chel; Yi, Junsin; Deshmukh, L.P.
Abstract: In the present work, we demonstrate the synthesis of Co1 -x Ni x S (0 ≤ x ≤ 0.2) metal chalcogenide thin films via a simple, inexpensive solution growth process and its subsequent studies aiming towards supercapacitive application. The as-prepared Co1- x Ni x S thin films revealed microstructure similar to spirulina algae-like nanowires with uniform substrate coverage. The highest average, total roughness and particle height values were observed from atomic force microscopy measurement for x = 0.05 composition. The electrochemical measurements on thin-film electrodes have been done via cyclic voltammetry, galvanostatic charge-discharge studies, and electrochemical impedance spectroscopy. The as-grown Co1- x Ni x S ( x = 0.05) thin-film electrodes demonstrated a reversible electrochemical feature, offers a high specific capacitance of 880 F g −1 at 6 mA cm −2 current density and cycling stability of 79% after 5000 cycles. This performance of Co1- x Ni x S electrodes at x = 0.05 was credited to its porous and large accessible area of entangled nanowire structure and effective intercalation of electrolyte ions through the electrode. This report opens new opportunities for the development of the metal chalcogenide thin films for high capacity electrochemical devices. Highlights: SEM study shows spirulina algae-like microstructure with a high surface area. The work function and contact potential affect the supercapacitor performance. A high surface potential observed by EFM study is favorable for high Cs at x = 0.05. A SC of 880 F g −1 is obtained at a current density of 6 mA cm −2 for x = 0.05. Excellent cycle stability of 79% seen after 5000 cycles.